Nacella EDGARI - González-Wevar, Claudio A.; Hüne, Mathias; Rosenfeld, Sebastián; Nakano, Tomoyuki; Saucède, Thomas; Spencer, Hamish; Poulin, Elie (Zenodo, 2018)
NACELLA EDGARI (POWELL, 1957) (FIG. 11) Patella ( Patinella ) fuegiensis – Smith, 1879: 180, pl. 19, figs 14, 14a (not of Reeve). Nacella fuegiensis – Pilsbry, 1891: 121, pl. 49, figs 28, 29, 30, 31 (not of Reeve). Nacella ( Patinigera ) fuegiensis – Thiele, 1912: 234 (not of Reeve). Patinigera fuegiensis edgari Powell, 1957: 127, pl. 2, figs 5, 6; Powell, 1960: 129. Nacella ( Patinigera ) edgari – Powell, 1973: 196, pl. 179, figs 3, 4; Cantera & Arnaud, 1985: 35; Troncoso et al. , 2001: 88. Nacella ( Patinigera ) macquariensis – Powell, 1973: 196 (in part, not of Finlay). Nacella cf. macquariensis – González-Wevar et al. , 2010: 116 (not of Finlay). Nacella edgari – González-Wevar et al. , 2016b: 2; 2017: 862. Material studied: Port-aux-Français, Kerguelen Islands (49°21’09.84’’ S, 70°13’05.89’’ E) N = 40; Port Christmas, Kerguelen Islands (48°41’40.22’’ S, 69°01’15.54’’ E) N = 50; Fjord des Portes Noires, Kerguelen Islands (49°29’47.32’’ S, 69°08’06.70’’ E) N = 30; Îles du Prince-de-Monaco, Kerguelen Islands (49°36’47.24’’ S, 69°14’11.38’’ E) N = 50; Baie des Cascades, Kerguelen Islands (49°10’02.31’’ S, 70°08’53.33’’ E) N = 30; Atlas Cove, Heard Islands (53°01’27.99’’ S, 73°23’46.95’’ E) N = 5. Shell: The shell shape and sculpture are variable in the species and two different morphologies were recorded at Kerguelen (Fig. 11A, B) and Heard Islands (Fig. 11C), respectively. Individuals from the Kerguelen Islands exhibit a conical morphology, dorsally depressed, with a thin and translucent shell. The anterior part of the animal is laterally compressed (Fig. 11D–F). The shell is of medium size (maximum length 80 mm) and has a low profile. The apex is located at the anterior 20–30% of the shell. All the slopes of the shell are concave. The aperture is oval. The whole surface is crowded with concentric lamellae that undulate as they cross the radials. The margin of the shell is very crenulated. The external coloration varies in the species across its distribution (brown, grey and purple) and the apex has a ...